Penerapan metode design thinking pada perancangan ui/ux website pet and care - Wijiyanto , Dwi; Laily Fithri, Diana (Computer Science and Information Technology, 2024)
Humans, as social beings, not only interact with one another but also with animals. The presence of pets is often utilized to support various activities, such as reducing stress, pursuing hobbies, and providing companionship in daily life. However, new challenges have emerged, including difficulties in caring for animals, limited access to nutritional needs for pets, and a lack of accurate information.with the advancement of digital technology, there are significant opportunities to enhance services in the field of pet care through technology-based innovations. This research aims to address these issues through the development of a digital platform in the form of the Pet and Care website, utilizing the Design Thinking method. This method was chosen for its user-oriented approach, which allows for the creation of solutions that align with the needs and expectations of users. The results of the study indicate that the developed platform successfully meets user needs, with an average satisfaction level of 52%, reflecting a positive user experience.